1960
DOI: 10.1039/jr9600002151
|View full text |Cite
|
Sign up to set email alerts
|

434. Reactivity of anions towards electron transfer in the bismuth ? tervalent bismuth exchange reaction

Abstract: The pseudo-capacity and over-all polarisation resistance during the electroreduction of tervalent bismuth at a dropping-mercury cathode in various media were traced as a series combination; and the general features of the former are described. The combination corresponding to the peak values was then balanced against the equivalent of a simple model of the faradaic admittance, and in this way information was obtained from which the specific rate constant for the above exchange in each medium could be evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The influence of supporting electrolytes on the rate and mechanism of electroreduction of Bi(III) ions on mercury electrodes was the subject of many studies 49. Special focus was on complexing media, such as halide, nitrate and sulfates 49, because of the increased rate of reversibility of Bi(III) electroreduction in those media.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of supporting electrolytes on the rate and mechanism of electroreduction of Bi(III) ions on mercury electrodes was the subject of many studies 49. Special focus was on complexing media, such as halide, nitrate and sulfates 49, because of the increased rate of reversibility of Bi(III) electroreduction in those media.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of either SO 2¹ 4 ions [13] or NO ¹ 3 ions [14] to the perchlorate supporting electrolyte also accelerates the reduction process of Bi III , although to a lesser extent than Cl ¹ ions. The order of the activity of those ions is [13]:…”
Section: Introductionmentioning
confidence: 99%
“…In this case it is that the reduction of metal ions of oxidation state three is not reversible in "non-complexing" media such as perchlorate at moderate ionic strengths (around 1 M) and this also pertains to Bi(III). [30][31][32][33] It was shown that the rate of electron transfer for Bi(III) reduction in highly acidic solutions increased with the addition of the following anions in solution: ClO 4  < NO 3  < Cl  . 31 Interestingly, at very high HClO 4 concentrations (8 M) the reduction of Bi(III) becomes fully reversible, 34 as well as in solutions of 1 M HClO 4 + 7 M NaClO 4 when using DC polarography.…”
mentioning
confidence: 99%
“…[30][31][32][33] It was shown that the rate of electron transfer for Bi(III) reduction in highly acidic solutions increased with the addition of the following anions in solution: ClO 4  < NO 3  < Cl  . 31 Interestingly, at very high HClO 4 concentrations (8 M) the reduction of Bi(III) becomes fully reversible, 34 as well as in solutions of 1 M HClO 4 + 7 M NaClO 4 when using DC polarography. 35 When solutions of 1 M HClO 4 with varying concentrations of NaClO 4 (1 to 8 M) were studied it was clear that the half-wave potential was dependant on ionic strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation